Establishment of a prognostic nomogram based on the clinical and inflammatory parameters as well as acute radiation enteritis for patients with cervical cancer receiving radiotherapy - Hu, Jing; Shi, Qianjin; Gong, Xiaoqin; You, Tao; Dai, Chunhua; Chen, Fei (Frontiers in Oncology, 2024)
ObjectiveAcute radiation enteritis is one of the most common complications of radiotherapy for patients with cervical cancer. This study aims to investigate the effect of acute radiation enteritis on the prognosis of patients with cervical cancer receiving radiotherapy and to establish a nomogram predicting the patients’ overall survival (OS).MethodsThe clinical data of 288 patients with cervical cancer who were admitted to our department from 2014 to 2020 were retrospectively analyzed, and the survival of patients were followed up. The Kaplan-Meier method was used to calculate the survival rate and for univariate analysis, and the Cox regression model was used for multivariate prognostic analysis. A nomogram survival prediction model was established based on independent risk factors, and the concordance index (C-index), receiver operating characteristic (ROC) curve and calibration curve were used to evaluate the predictive accuracy of the model. The clinical applicability of the model was assessed by the decision curve. External validation of the nomogram prediction model was performed in 74 patients admitted to our hospital from 2020 to 2021.Results60 patients (20.8%) developed grade 2 or higher acute radiation enteritis. The 1-, 3-, and 5-year OS rates were 94.4%, 80.9%, and 77.4%, respectively. Multivariate Cox regression analysis showed that: Age ≥ 60 years, diabetes/hypertension, anemia, FIGO stage III-IV, poor differentiation, pelvic lymph node metastasis, NLR ≥ 2.54 and grade 2 or higher acute radiation enteritis were independent risk factors for OS in cervical cancer patients undergoing radiotherapy (P < 0.05). The C-index of OS nomogram model was 0.815 (95% CI: 0.766-0.864). The AUC of 3-year and 5-year OS were 0.849 (95%CI: 0.789-0.909) and 0.840 (95%CI: 0.782-0.899), respectively. The AUC value of 3-year OS in the external validation set was 0.779 (95%CI: 0.635-0.922). The calibration curve showed that the model was well calibrated, and the decision curve verified the clinical applicability of the constructed nomogram.ConclusionThis study established an accurate predicting nomogram based on independent prognostic factors in cervical cancer patients receiving radiotherapy, and patients with grade 2 or higher acute radiation enteritis should be paid more attention to in clinical practice.